Metabolomics study of treatment response to conbercept of patients with neovascular age-related macular degeneration and polypoidal choroidal vasculopathy - Yinchen Shen; Yinchen Shen; Yinchen Shen; Yinchen Shen; Yinchen Shen; Hanying Wang; Hanying Wang; Hanying Wang; Hanying Wang; Hanying Wang; Xiaoyin Xu; Xiaoyin Xu; et al. (Frontiers in Pharmacology, 2022)
Graphical AbstractAMD, age-related macular degeneration; PCV, polypoidal choroidal vasculopathy; PLS-DA, partial least squares discriminant analysis; LPC, lysophosphatidylcholine; PC, phosphocholine; ROC, operating characteristic curve; AUC, area under the receiver operating characteristic curve; vWF, von Willebrand Factor. Note: The protein structure of vWF is downloaded from PDB (https://www.rcsb.org/).